Caractérisations Structurale, Floristique Et Biomasse Ligneuse Du Peuplement À Hagenia abyssinica Du Parc National De Kahuzi-Biega (Rift Albertin, RDC) - Imani Mugisho Gérard; Zapfack Louis; Mangambu Mokoso Jean De Dieu; Penedimanja Pancrace; Mwanga Mwanga Ithe Jean-Claude; Boyemba Faustin; Amani Christian (European Scientific Journal, ESJ, 2016)
Hagenia abyssinica is a characteristic species of mountain forests in the Albertine Rift. In Kahuzi Biega National Park, the species is found between 2000 and 2600 m altitude. This study intended to characterize Hagenia monospecific forest by providing an account for its floristic composition, structure and biomass. Data were collected from 9 different plots of 1 hectare each located in 3 different sites (Tshivanga 2000-2250m asl; Mugabe and Kasirusiru 2400-2600m asl). Parameters including tree diameter ≥ 10cm, height, dead individuals and young shoots of Hagenia abyssinica were wetting the plot. The results showed that species richness was significantly low, varying between 8-24 species (p < 0.05, Df = 35); while the specific density was 565 ± 121 individuals. The Richness decreased with the increment of the species density of Hagenia. The similarity analysis revealed the influence/impact of the site/altitude on the species composition. The diametric structure showed a regressive dynamism within the population found between 2000 and 2200 m altitude, in which Hagenia specimens were replaced by the specimens of secondary forest species such as Sapium ellipticum, Macaranga neomilbraediana, Neoboutonia macrocalyx. Whereas, between 2400-2600 m altitude, there was a progressive dynamism with several Hagenia young shoots, with no mortality (χ2 = 487, p < 0.001). The average woody biomass was estimated at 108t / ha. This increased as Hagenia density decreased and vegetation became heterogeneous. Human disturbance and climate change effects in the region, could be the causes of variability observed in this population in the Kahuzi-Biega National Park.